Endothelin‐1 dependent expression of GAG genes involves NOX and p38 mediated Smad linker region phosphorylation. (17th May 2022) - Babaahmadi‐Rezaei, Hossein; Mohamed, Raafat; Dayati, Parisa; Mehr, Reyhaneh Niayesh; Seif, Faezeh; Sharifat, Narges; Khedri, Azam; Kamato, Danielle; Little, Peter J.
Abstract: Endothelin‐1 (ET‐1) is implicated in the development of atherosclerosis and mediates glycosaminoglycan (GAG) chain hyperelongation on proteoglycans. Our aim was to identify the ET‐1‐mediated signalling pathway involving NADPH oxidase (NOX), p38 MAP kinsae and Smad2 linker region phosphorylation (phospho‐Smad2L) regulate GAG synthesising enzymes mRNA expression (C4ST‐1 and ChSy1) involved in GAG chains hyperelongation in human vascular smooth muscle cells (VSMCs). Signalling intermediates were detected and quantified by Western blotting and the mRNA levels of GAG synthesising enzymes were assessed by quantitative real‐time polymerase chain reaction (qRT‐PCR). ET‐1 treatment of human VSMCs resulted in an increase in phospho‐Smad2L level. The TGF‐β receptor antagonist, SB431542 and the mixed ETA and ETB receptor antagonist bosentan, inhibited ET‐1‐mediated phospho‐Smad2L level. In the presence of apocynin and diphenyleneiodonium chloride (DPI) (NOX inhibitors) and SB239063 (p38 inhibitor) ET‐1‐mediated phospho‐Smad2L levels were inhibited. The gene expression levels of GAG synthesising enzymes post‐ET‐1 treatment were increased compared to untreated controls ( p  < 0.01). The ET‐mediated the mRNA levels of these enzymes were blocked by the bosentan, SB431542, SB239063, DPI, apocynin and antioxidant N‐acetyl‐L‐cysteine (NAC). ET‐1‐mediated signalling to GAG synthesising enzymes gene expression occurs via transactivation‐dependent pathway involving NOX, p38 MAP kinsae and Smad2 linker region phosphorylation. Abstract : Schematic diagram illustrating the proposed ET‐1 signalling pathway involving NOX and phospho‐p38 intermediates and Smad linker region to stimulate ChSy‐1 and C4ST‐1 mRNA expression. ET‐1‐mediated phosphorylation of Smad2 linker region in human VSMCs is mediated by transactivation of TβR1. Stimulation of Smad2 linker region phosphorylation through NOX/ p38 MAP kinase leading to ChSy‐1 and C4ST‐1 mRNA expression.